Pengaruh Kompetensi dan Beban Kerja Terhadap Kinerja Pegawai dengan Mediasi Komitmen Organisasional - Sobirin; Suhana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of competence and workload on employee performance, with organizational commitment as a mediating variable at PT BPR BKK Purwokerto (Perseroda). This study uses a quantitative approach with primary data of 118 respondents. Data analysis was carried out using SPSS software with multiple linear regression methods and the Sobel test to test the mediation effect. The results of the study indicate that competence has a significant positive effect on performance. Workload has a significant negative effect on performance. Competence has a significant positive effect on organizational commitment. Workload has a significant negative effect on organizational commitment. Organizational commitment has a significant positive effect on performance. Organizational commitment mediates the influence of competence and workload on performance. This study has theoretical and practical implications.